PENGARUH PERSEPSI MAHASISWA AKUNTANSI TENTANG PAJAK DAN BREVET PAJAK TERHADAP MINAT BERPROFESI DIBIDANG PERPAJAKAN - Asep Suherman (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2019)
Abstract       This research was counducted at the  University of Pamulang the purpose of this study was to determine the effect of Accounting Students' Perceptions of Taxes and Taxes on Profession Interest in Taxation. The results of this study indicate that Perceptions about Tax have a partially positive effect on Interest in Profession in the Taxation Sector. F there is a significant influence between X1 and X2 simultaneously on the interests of working in the taxation field. Perception of Tax and Brevet tax in the Adjusted R Square Test of 0.114 means that the variable of interest in the taxation profession can be explained by the perception variable about tax and tax brevet of 11.4% or it can be said that the variable perception of tax and tax brevet can influence interest in the profession taxation of 11.4%.